The effects of compost application on growth performance of aerobic rice grown in sandy soil / Ummi Farhani Azreen Aziz - Azreen Aziz, Ummi Farhani (Faculty of Plantation and Agrotechnology, 2016)
Aerobic rice cultivation is a new concept of growing rice with supplemental irrigation without the necessity for standing water in the field. Soil compost application is a common soil management practice used to improve the characteristics and fertility of sandy soil in order to increasing of water holding capacity (WHC), cation exchange capacity (CEC), nutrient retention and microorganisms activity. A set of experiment was conducted to determine the effectiveness of compost materials used as a treatment. Aim of the study is to identify the effects of compost on growth performance of aerobic rice grown in sandy soils. This study was conducted with five rate of compost treatments each with three replication arranged by Complete Randomized Design (CRD). The responses of aerobic rice on compost were measure based on plant height, number of leaves, number of tiller and number of panicle of growth through out 60 days of growing periods. At the end of the experiment, it determines that the different rate of compost were give a significant effects towards growth parameters and yield measurement of paddy based on plant height, number of leaves, number of tillers and number of panicles and dry weight grain production. Overall of this study, the recommended rate for compost treatment is 109 per lkg soil which is equal to 5000kg per hectare of compost material apply at actual paddy field area.